Analisis nilai perusahaan ditinjau dari profitabilitas, struktur aset, pertumbuhan penjualan, kebijakan dividen dan struktur modal pada perusahaan sektor property dan real estate - Mariani, Desy; Suryani, Suryani; Anggraeni, Desy (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of profitability, asset structure, sales growth, dividend policy, and capital structure on firm value in property and real estate sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period of 83 companies. The data used in this study were obtained from financial statement data and annual reports. The population in this study are property and real estate sector companies listed on the Indonesian Stock Exchange. The sampling technique used was the purposive sampling method and obtained 230 sample data from 46 companies. The analysis technique used in this study is multiple linear regression analysis using the Statistical Package for the Social Sciences (SPSS) version 22. The results of this study indicate that dividend policy and capital structure have a positive and significant effect on firm value, while profitability, asset structure, and sales growth have no effect on firm value.